Identifying the factors that contribute to divorce rate among muslim’s couples in Terengganu / Mohd Khairul Hilmi Abdul Rasid - Abdul Rasid, Mohd Khairul Hilmi (2016)
The purpose of this study is to know the factors of the divorce rate among Muslim’s couples in Terengganu. Based on the time series data for 32 years from 1983 to 2014, the data has been analysed using SPSS program. Three independent variables has been chosen to be tested; female labor force participation rate, unemployment rate and educational attainment. Multiple regression analysis has been used to analyse the model. The result suggest that there is a negative significance influence between female labor force participation rate and divorce rate while unemployment rate and educational attainment have a positive significance influence with the divorce rate respectively. However, there is one variable that has no significant influence towards the divorce rate; female labor force participation rate. This study confirms that unemployment rate and educational attainment are the determinants of the Muslim’s divorce rate in Terengganu